Plant species diversity of pastures in the Naryn Oblast (Kyrgyzstan) - Hoppe, Franziska; Schickhoff, Udo; Oldeland, Jens (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
Traditional pastoral practices in Kyrgyzstan have been transformed into more intensive forms of pastoral land use during the Soviet colonial period, and once again modified after independence in 1991. Kyrgyz winter pastures close to settlements are subject to degradation processes, while remote summer pastures are less affected. It is largely unknown to what extent current grazing regimes, repeatedly modified during the post-Soviet transformation process, have influenced plant species diversity of mountain pastures. This paper aims to analyze inventory (α) and differentiation (β) diversity of pastures in the Naryn Oblast, where winter pastures are subject to increased grazing pressure. We used a non-asymptotic approach in order to infer Hill numbers, i.e. the effective number of species at different levels of q (where q = 0: species richness, q = 1: Shannon diversity, q = 2: Simpson diversity) to make fair comparisons among assemblages of winter and summer pastures. We established sample-size-based rarefaction (interpolation) and prediction (extrapolation) curves, and assessed beta diversity by implementing an ANOSIM and by calculating Jaccard and Sørensen indices. We also inspected the occurrence of rare endemic plants, which might play a key role in local ecosystem processes and are important for biodiversity conservation. Increased grazing pressure on winter pastures mainly results from abandoned seasonal livestock migration and unbalanced grazing intensity between seasonal pastures. Our results show that inventory diversity is higher on summer pastures and that species composition between summer and winter pastures differs significantly. Winter pastures are less species-rich but have a higher percentage of rare endemic species.